The Educational Role of Children's Programs in Libyan TV An Analytical -Field Study of "Flowers of Life" Program - فلحي, محمد جاسم; حمد سعيد, سعيد مفتاح (ALBAHITH ALALAMI, 2015)
Television contributes children the acquisition of knowledge, moral and social values through programs that are offered to them and the extent of the focus on the effective aspects of life in the age of the target stage. The subject of this research aims to know the children programs in Libya television through a comprehensive analytical study of the program entitled “zihur al-hayat” within the broadcast season from April 1, 2004 to June 30, 2004. It also focuses on trying to identify the Libyan television policy in broadcast educational content through the children's programs in the prevailing political and social conditions during the period of study as well as knowing the opinions of the children's sample under study in Al-Baidhaa – a Libyan city – and their views towards all the programs generally and towards “zihur alhayat” particularly. This study aims at identifying the role of this program in broadcasting educational, social and moral values and the relationship between this program and the educational and social aspects in Libya. This research is one of few researches focusing on the programs of children. It includes three parts. Part one includes methodological framework, identification of the problem, importance of the study, its aims, methods by which the sample is chosen. Part two discusses the development of Libyan television and the emergence of the kids programs in Libyan television. Part three analyses the results of the applied study.